Traditional Chinese Medicine hot pack technology for a patient with arthralgia and related nursing measures (中药热奄包技术治疗1例尪痹患者的护理体会) - KAI Yan (凯艳); TANG Ling (唐玲); LU Lin (芦琳); LI Suqian (李苏茜) (中西医结合护理)
To summarize the therapeutic effect of Traditional Chinese Medicine(TCM) hot pack technology in treating arthralgia, and summarized related nursing measures. The patient received the TCM hot pack technology on the basis of nursing evaluation and diagnosis. Targeted nursing interventions on activity of daily living, nutrition, psychological health and functional exercise were also carried out to relieve the pain and improve the quality of life. (本文总结中药热奄包技术治疗1例尪痹患者的护理经验, 通过护理评估、护理诊断, 制定生活、饮食、心理、功能锻炼等针对性护理计划, 并实施中药热奄包治疗, 患者疼痛明显减轻, 生活质量明显改善。)